All Printable Perovskite Solar Modules with 198 cm2 Active Area and Over 6% Efficiency. Issue 11 (13th August 2018) - De Rossi, Francesca; Baker, Jenny A.; Beynon, David; Hooper, Katherine E. A.; Meroni, Simone M. P.; Williams, Daniel; Wei, Zhengfei; Yasin, Amrita; Charbonneau, Cecile; Jewell, Eifion H.; Watson, Trystan M.
Abstract: Perovskite solar cells based on an all printable mesoporous stack, made of overlapping titania, zirconia, and carbon layers, represent a promising device architecture for both simple, low‐cost manufacture, and outstanding stability. Here a breakthrough in the upscaling of this technology is reported: Screen printed modules on A4 sized conductive glass substrates, delivering power conversion efficiency (PCE) ranging from 3 to 5% at 1 sun on an unprecedented 198 cm 2 active area. An increase in the PCE, due to higher V OC and fill factor, is demonstrated by patterning the TiO2 blocking layer. Furthermore, an unexpected increase of the performance is observed over time, while storing the modules in the dark, unencapsulated, at ambient conditions (with humidity increasing from 30 and 70% RH), resulting in 6.6% PCE and 6.3% stabilised at V max measured after over two months since fabrication. Equally impressive is the low light performance with 11 and 18% PCE achieved respectively at 200 and 1000 lux under fluorescent lighting. It is hoped that this demonstration of good performance on large area can unlock the viability of perovskite solar cells manufactured on an industrial scale. Abstract : Low‐cost materials and equipment are used to demonstrate large area screen printed perovskite solar modules, advancing the route to commercialization of these solution processed devices. The screen printing process is optimized to avoid defects caused by printing such large areas. The resulting module with an efficiency of 6.3% is world leading for a device of this size.